A novel approach for antibody nanocarriers development through hydrophobic ion-pairing complexation. (September 2014) - Patel, Ashaben; Gaudana, Ripal; Mitra, Ashim K.
Abstract IgG-Fab fragment, a model antibody protein was hydrophobically modified by a novel approach of ion-pairing complexation. Three different sulphated ion-pairing agents were utilised including sodium dodecyl sulphate, taurocholic acid and dextran sulphate (DS). The formations of hydrophobic ion-pairing (HIP) complexes were dependant on pH and molar ratio of ion-pairing agent to Fab. Aqueous solubilities of HIP complexes were very low compared to Fab alone. In particular, when dextran sulphate was added as ion-pairing agent, formed Fab:DS HIP complexes were least soluble in water. Further, nanoparticles (NPs) loaded with drug and Fab:DS HIP complex were prepared and characterised with respect to encapsulation efficiency and size. We observed significant improvement in encapsulation efficiency for Fab:DS HIP complex-loaded nanoparticles. This study demonstrates a novel approach of formulating antibody-loaded nanoparticles which can also be employed for delivery of large antibodies.